Been wrong so long it feels like right [large type] - Mosley, Walter (Mosley, Walter. King Oliver novel., 2025)
In this third installment in Mosley's series, "a family member's terminal illness leads P.I. Joe King Oliver to the investigation of his life: tracking down his long-lost father; and meanwhile, a new case pits King's professional responsibility against his own moral code"--